FMCG Products Manufactured with Essential Oils as Active Ingredients - Mohd. Murray, Hunter, Assoc. Prof.; Noor Azman, Zainal Abidin (Malaysian Association of Research Scientists (MARS), 2010)
Mohd. Murray Hunter and his team won bronze at Malaysia Technology Expo (MTE) 2007, 29th - 31st Mac 2007 at Putra World Trade Centre (PWTC), Kuala Lumpur. MTE 2007 organized by MARS and PROTEMP Exhibition.